UJI EFEKTIVITAS EKSTRAK BUAH BALONGGA (Cucumis melo L. forma agrestis) SEBAGAI INSEKTISIDA ALAMI TERHADAP NYAMUK Aedes sp. - Sri Aprilianti Idris (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2021)
Background: Aedes sp is a vector of Dengue Hemorrhagic Fever (DHF). DHF is a disease caused by the dengue virus of the genus Flavivirus, family Flaviviridae. DHF is transmitted from person to person through the bite of the Aedes aegypti and Aedes albopictus (female) mosquitoes. Balongga fruit is a wild plant typical of Southeast Sulawesi which is usually consumed by the people of Southeast Sulawesi as a food ingredient such as vegetables and to add flavor to fish dishes. Balongga fruit contains secondary metabolites, namely flavonoids, saponins and tannins which have the ability to inhibit the growth of larvae and mosquitoes.Objective: The purpose of this study was to determine the results of the effectiveness test of the extract of Balongga fruit (Cucumis melo L. forma agrestis) as a natural insecticide against Aedes sp.Methods: This research was conducted experimentally, in the test using four treatments with variations in concentration, namely 20%, 40%. 60% and 80%, negative control (aquadest) and positive control X-Electric (transflutrin 12.38 g/l)), and the number of mosquitoes used was 25 in each treatment with three repetitions. The observation time required in this study is 1440 minutes. Observations were also made by counting the dead mosquitoes in each treatment with time intervals of 5, 10, 20, 40, 60, 120, 240, 480, and 1440 minutes. The data in this study were analyzed using the one-way ANOVA test.Conclusion: The results showed that the 80% concentration of Balonga fruit flesh extract was the most effective as a natural insecticide to kill Aedes sp mosquitoes with an interval of 240 minutes.